Subcutaneous hydatid cyst in forearm a diagnostic dilemma with neurofibroma (Bangladesh Journal of Medical Science, 2016)
Hydatid disease caused by larval stage of Echinococcus granulosus usually affects lungs and liver of human and animals. Affection of subcutaneous tissue is rare; though not rarest but often clinically mistaken as neurofibroma or lipoma. Preoperative diagnosis is mandatory to avoid surgical contamination or future accidents. Two middle aged males presented with forearm nodules and one female presented with an arm nodule; all of which on needle aspiration cytology and wet smear examination provisionally diagnosed as hydatid cyst, later confirmed radiologically and surgically. Primary hydatid disease constitutes potentially serious differential diagnoses in subcutaneous swelling.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.634-636